The Compatibility of Listening Skills in Our Arabic Language Books for First Graders with Special Products in Jordan - Al-Hwieml, Omar (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to reveal the extent to which the listening skills included in the questions of the listening texts contained in our Arabic books for the first three grades align with the specific outcomes. Methods: The study used a descriptive analytical approach, and three lists were created for the analysis: the list of specific outcomes, the list of listening skills, and the classification of questions into essay and objective. Results: The results showed that there is a gap between the levels included in the listening text questions and the listening outcomes stated in the general framework document and the specific outcomes of the Arabic language study. The questions in the books for the three grades addressed only (8) out of (24) products, accounting for a percentage of (33%). The results also revealed a lack of inclusion of main and subsidiary listening skills. The questions in the first-grade book were limited to the first level (auditory excellence), and although the results showed some improvement in the questions of the second and third-grade books, they still lacked the classification skill and the transformation of questions into essay and objective. The results predominantly focused on essay questions, which accounted for (148) questions, representing (81%) of the total. Conclusions: There is a need to reconsider the listening questions to better align with the listening outcomes stated in the general framework document for curricula. Additionally, it is important to adopt a scientific methodology when developing listening questions to achieve balance and progression in the forms of objective questions.